(untitled) (Intent Research Scientific Journal, 2025)
Targeted scientific research is being conducted around the world to create resource-saving technologies for preparing fields for sowing before sowing seeds of agricultural crops and new models of technical means for their implementation, to develop scientific and technical foundations for improving existing ones, and to ensure resource efficiency in the work process. Development of agrotechnical demonstrators of existing chisel cultivators and the development of material and energy efficiency savings methods and, in this regard, the development of a construction scheme for chisel cultivation